Role of Green Intellectual Capital and Green Innovation to Corporate Economic Sustainability - Yerisma Welly; Martin Yehezkiel Sianipar; Novi Darmayanti; Arthur Simanjuntak; Muhammad Isa Alamsyahbana (Jurnal Akuntansi Manado (JAIM), 2023)
The purpose of this study was to determine the effect of GIC and GI on CES. The research focused on consumer goods sector listed on the IDX for 2018-2022 period with a sample of 42 companies. The research method uses quantitative data analysis with a panel data regression analysis approach. Findings reveal a significant and positive relationship between GIC and CES. GIC enables companies to adopt sustainable business practices, which increases company profitability. GIC provides a competitive advantage in managing environmental risks, meeting customer demands regarding environmental issues, and adapting to changes in regulations related to sustainability. However, the results also show a significant negative impact of GI on CES. GI may lead to a decline in CES in the short term because significant financial resources are required to implement green innovations, which can reduce a company's financial elasticity. This can force companies to abandon profitable production and investment activities.